Anais do II Encontro Regional do PET-Saúde Equidade na Fronteira Oeste: mulheres no SUS: corpos que cuidam, vozes que transformam - (:unkn) unknown (Universidade Federal do Pampa, 2026)
The Proceedings of the II Regional Meeting of PET-Health Equity on the Western Border, held at the Federal University of Pampa (UNIPAMPA), brought together scientific productions and experience reports focused on promoting equity, valuing women within the Brazilian Unified Health System (SUS), and strengthening the integration between education, healthcare services, and the community. The event’s central theme, “Women in SUS: bodies that care, voices that transform,” addressed issues related to mental health, working conditions, social justice, diversity, interdisciplinarity, and innovation in healthcare. The presented studies included qualitative research, literature reviews, experience reports, and extension activities developed in Primary Health Care, mental health, the prison system, health education, and professional training. Special emphasis was given to initiatives aimed at promoting gender equity, strengthening women’s protagonism in scientific production, valuing cultural and religious diversity, and developing educational technologies and interdisciplinary care strategies. The findings highlight the importance of collaborative practices, critical professional training, and the strengthening of public health policies to consolidate the principles of comprehensiveness, universality, and equity within SUS. It is concluded that the event represented an important space for the exchange of knowledge and experiences, contributing to the education of professionals committed to humanized care, social justice, and the transformation of healthcare practices.
Proceedings of the II Regional Meeting of PET-Health Equity on the Western Border: women in SUS: bodies that care, voices that transform
Keywords: Health Equity; Mulheres na Saúde; Políticas Públicas de Saúde; Humanização do Cuidado; Saúde Mental; Práticas Interdisciplinares; Educação em Saúde; Sistema Único de Saúde; Health Education; Humanized Care; Mental Health; Public Health Policies; Interdisciplinary Practices; Unified Health System (SUS); Women in Health; CIENCIAS DA SAUDE